2017
DOI: 10.1007/s10067-017-3616-7
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic meningitis in relapsing polychondritis: a case report and literature review

Abstract: Aseptic meningitis is an extremely rare neurologic complication of relapsing polychondritis (RP). We reported a case of a 58-year-old Chinese female with intractable headache, puffy ears, pleocytosis, and cranial magnetic resonance imaging (MRI) showing thickened and enhanced meninges. She was finally diagnosed of aseptic meningitis due to RP after full exclusion of infectious causes. She gradually developed neurosensory hearing loss, vertigo, and saddle nose while glucocorticosteroid therapy and combined cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Neurologic presentation of meningoencephalitis with RP varied between cases; reported presentations were hearing loss, unsteadiness, personality changes, generalized tonic-clonic seizure, impaired cognitive function, impaired visual acuity, confusion, memory loss, unstable gait, ataxia, hydrocephalus, delirium, cerebral infarction, coordination problems, distraction, word finding difficulty, emotional lability, abducens nerve palsy, anxiety, insomnia, memory loss, deafness, gait change, urinary incontinence, expressive and receptive aphasia, dullness, acalculia, and papilledema [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurologic presentation of meningoencephalitis with RP varied between cases; reported presentations were hearing loss, unsteadiness, personality changes, generalized tonic-clonic seizure, impaired cognitive function, impaired visual acuity, confusion, memory loss, unstable gait, ataxia, hydrocephalus, delirium, cerebral infarction, coordination problems, distraction, word finding difficulty, emotional lability, abducens nerve palsy, anxiety, insomnia, memory loss, deafness, gait change, urinary incontinence, expressive and receptive aphasia, dullness, acalculia, and papilledema [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 of 19 cases improved on glucocorticoids and 5 out of those 10 showed a relapse of disease. Cyclophosphamide was added to glucocorticoids in 3 cases, one case died [ 7 ], one improved with no relapse [ 8 , 9 ], and the most recent case had to add cyclosporin A to relieve symptoms, even though the patient relapsed [ 6 ]. Azathioprine was added to glucocorticoids in 4 cases all of which showed improvement, but three of those cases relapsed [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that CNS involvement occurred in 8–12% of RP patients [ 2 , 4 , 13 , 16 ] and the mortality rates were high [ 13 , 18 , 22 , 23 ]. When we reviewed the literature [ 18 , 22 42 ], 14 of 50 RP patients (28%) with meningitis/encephalitis developed neurological symptoms preceding any detectable chondritis (Table 4 ). At the last follow-up, 82 and 18% of the patients with CNS involvement were allocated to AL and BL subgroups, respectively (Table 4 ), consistent with our finding of close relationship between auricular involvement and CNS involvement [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“… a A review of the literature was conducted on RP meningitis/encephalitis using PubMed [ 18 , 22 42 ] b Time interval (months) between the onset of meningitis/encephalitis and that of chondritis c Follow-up duration of patients (months) d Age, time interval, and follow-up duration were expressed as mean ± standard error of the mean e NA, Not applicable …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation